Antibacterial, Antifungal, and Antioxidant Activities of Silver Nanoparticles Biosynthesized from Bauhinia tomentosa Linn - Senthil Renganathan; Sugunakala Subramaniyan; Nivetha Karunanithi; Preethi Vasanthakumar; Arne Kutzner; Pok-Son Kim; Klaus Heese (MDPI AG, 2021)
The biogenic synthesis of silver nanoparticles (AgNPs) has a wide range of applications in the pharmaceutical industry. Here, we synthesized AgNPs using the aqueous flower extract of Bauhinia tomentosa Linn. Formation of AgNPs was observed using ultraviolet-visible light spectrophotometry at different time intervals. Maximum absorption was observed after 4 h at 420 nm due to the reduction of Ag+ to Ag0. The stabilizing activity of functional groups was identified by Fourier-transform infrared spectroscopy. Size and surface morphology were also analyzed using scanning electron microscopy. The present study revealed the AgNPs were spherical in form with a diameter of 32 nm. The face-centered cubic structure of AgNPs was indexed using X-ray powder diffraction with peaks at 2θ = 37°, 49°, 63°, and 76° (corresponding to the planes of silver 111, 200, 220, 311), respectively. Energy-dispersive X-ray spectroscopy revealed that pure reduced silver (Ag0) was the major constituent (59.08%). Antimicrobial analyses showed that the biosynthesized AgNPs possess increased antibacterial activity (against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative), with larger zone formation against S. aureus (9.25 mm) compared with that of E. coli (6.75 mm)) and antifungal activity (against Aspergillus flavus and Candida albican (with superior inhibition against A. flavus (zone of inhibition: 7 mm) compared with C. albicans (zone of inhibition: 5.75 mm)). Inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity was found to be dose-dependent with half-maximal inhibitory concentration (IC50) values of 56.77 μg/mL and 43.03 μg/mL for AgNPs and ascorbic acid (control), respectively, thus confirming that silver nanoparticles have greater antioxidant activity than ascorbic acid. Molecular docking was used to determine the mode of antimicrobial interaction of our biosynthesized B. tomentosa Linn flower-powder extract-derived AgNPs. The biogenic AgNPs preferred hydrophobic contacts to inhibit bacterial and fungal sustainability with reducing antioxidant properties, suggesting that biogenic AgNPs can serve as effective medicinal agents.